The Role of Government Political Approaches in the Growth and Decline of Hardline Islamic Movements in Indonesia - Suwarno, Peter (Jurnal Sosiologi Agama Indonesia (JSAI), 2022)
One of the most arduous challenges in the development of Indonesian democracy has been the political contestation between the hardline Islamists vs. secular nationalists. This paper describes how the Indonesian governments dealt with this conflict due to the growing Islamic conservatism and the midst of democratization. For this purpose, this paper examines the controversial government policies during the administration of Soekarno, Soeharto, Soesilo Bambang Yudhoyono (SBY), and Joko Widodo, who governed Indonesia for at least two terms. The analysis of the data collected from various media and research publications describes and compares the political approaches of these presidents in dealing with hardline Islamic movements. Soekarno had to end his primary reliance on democratic debates that resulted in no agreement by issuing an authoritarian decree allowing him to ban the most powerful Islamist party – Masyumi. Soeharto, who implemented iron-fist policies against the Islamists, created stability for badly needed development, but to maintain his power, he had to meet some of the Islamic demands. Due to the reform era, SBY attempted to be more democratic toward the hardline Islamic appeals, leading to his indecisiveness that enhanced the growth of Islamic hardliners. Jokowi uses legal and discursive strategies to uphold secular nationalism. Still, to deal with Islamic radicalism, he used semi-authoritarian approaches such as banning hardline Islamic organizations. This paper concludes that the Indonesian liberal democratic political approaches could enhance Islamic politics and the growth of hardline Islamism. In contrast, authoritarian or semi-authoritarian approaches to secular nationalism created more stability for the growth of moderate Islam in Indonesia.